Diagnóstico de la implementación del SG-SST en las constructoras pioneras de Colombia (2020)
In the search for an ideal management methodology that allows especially the construction companies in Colombia to appropriate an effective tool that ensure an adequate Occupational Safety and Health Management System implementation in the projects they develop, the first objective of the research called “Management methodology for the implementation of the OHSMS in the pioneering construction companies in Colombia”, is the development of a diagnosis based on four approaches. The sample of the research are the pioneer construction companies of Colombia, which is conducted under an interview following the guidelines of the NTC-ISO 45001:2018 and the project management, with the purpose of gathering information that allows the consolidation of an effective methodology for the OSH implementation.